Randomised, double-blind study to evaluate the efficacy of rituximab in the treatment of idiopathic membranous nephropathy: A clinical trial protocol. - Shinobu Shimizu; Akihito Tanaka; Nao Matsuyama; Fumie Kinoshita; Kazuhiro Furuhashi; Shoichi Maruyama; PRIME Study Group (PLoS ONE)
In Japan, corticosteroid monotherapy has traditionally been recommended as the first-line therapy for membranous nephropathy with nephrotic syndrome. In contrast, except for Japan, rituximab is recommended as the first-line therapy for membranous nephropathy with nephrotic syndrome. This clinical trial aimed to verify the efficacy and safety of the intravenous administration of rituximab without steroids or immunosuppressants as an induction therapy in Japanese patients with idiopathic membranous nephropathy and nephrotic syndrome. This was a multicentre (15 in Japan), placebo-controlled, randomized, double-blind, parallel-group comparative study. A total of 88 patients diagnosed with idiopathic membranous nephropathy and nephrotic syndrome were randomly allocated to rituximab and placebo groups in a 1:1 ratio; rituximab 1,000 mg or placebo IV infusion was administered every 2 weeks for two doses in a double-blinded manner. The primary endpoint was the percentage of patients achieving less than 1.0 g/g creatinine in urine protein/creatinine ratio in random urine at 26 weeks after the first administration of rituximab or placebo. This study was approved by the institutional review boards and conducted in accordance with the Good Clinical Practice guidelines. This study was registered at ClinicalTrials.gov, NCT05914155 and the Japan Registry of Clinical Trials, jRCT2041230037 on 13 June 2023.